Transparency and authoritarian rule in Southeast Asia : Singapore and Malaysia - Rodan, Garry, 1955- (RoutledgeCurzon/City University of Hong Kong South East Asian studies, 2004)
This book rejects the notion that the 1997-98 Asian economic crisis was further evidence that ultimately capitalism can only develop within liberal social and political institutions.